EFEKTIVITAS PENERAPAN MANAJEMEN STRATEGI PADA DIGITAL MARKETING DI PT KARYA GIRI PALMA - Dominikus Bobby Dwi Setyawan; Indrawati Yuhertiana (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The research aims to analyze and evaluate the effectiveness of strategic management implementation on digital marketing at PT Karya Giri Palma, a furniture product company. The effectiveness of the implementation of strategic management in digital marketing using qualitative descriptive methods. Data sources are only through primary data with interview methods and observation methods, and using secondary data that obtain information such as the results of previous studies, journals and references. This research obtained results that show the implementation of strategic management in digital marketing that has been running effectively. In this study, the application of strategic management has several external and internal obstacles.